Tofacitinib for the Treatment of Severe Interstitial Lung Disease Related to Rheumatoid Arthritis - Caterina Vacchi; Andreina Manfredi; Giulia Cassone; Stefania Cerri; Giovanni Della Casa; Dario Andrisani; Carlo Salvarani; Marco Sebastiani (Case Reports in Medicine)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease characterized by chronic symmetrical erosive synovitis and extra-articular manifestations, including interstitial lung disease (ILD), whose treatment is nowadays challenging due to high infectious risk and possible pulmonary iatrogenic toxicity. Janus kinase inhibitors, namely, tofacitinib, baricitinib, and upadacitinib, are the latest drug class for the treatment of RA with a good safety profile. We present the case of a patient with RA-ILD successfully treated with tofacitinib. A 52-year-old man was referred to our multidisciplinary clinic for rheumatic and pulmonary diseases for an active erosive seropositive RA and progressive ILD. Previous treatments were GC, hydroxychloroquine, methotrexate, etanercept, withdrawn after ILD detection, and tocilizumab, discontinued due to relapsing infections. After our evaluation, we proposed rituximab in addition to low-dose GC and hydroxychloroquine, ineffective on joint involvement. Therefore, we proposed tofacitinib which allowed us to control joint involvement, stabilize ILD improving respiratory symptoms, and manage the frequent infectious episodes that occurred initially. The short half-life and rapid-acting of tofacitinib are two helpful characteristics regarding this aspect. Despite limited data from randomized trials and real-life, tofacitinib could represent a safe therapeutic option for RA-ILD patients. Longitudinal studies are required to confirm this encouraging report.